KEPEMIMPINAN GURU DALAM MENINGKATKAN PRESTASI BELAJAR FIKIH SANTRI: ANALISIS PENGARUH MODEL LEADERSHIP PENDIDIKAN DI PONDOK PESANTREN TAHFIDZUL QUR’AN ABI-UMMI BOYOLALI TAHUN AJARAN 2024/2025 - Kharina Putri; Ngatmin Abbas; Isfihani Isfihani (STKIP Pesisir Selatan, 2025)
This study aims to analyze the influence of teacher leadership on the learning achievement of eighth-grade students in the Fiqh subject at the Tahfidzul Qur’an Abi-Ummi Islamic Boarding School, Boyolali, during the 2024/2025 academic year. The research is grounded on the importance of teachers as learning leaders who not only transfer knowledge but also shape students’ character and learning motivation within an Islamic education framework. The study employs a quantitative approach with an associative design. The population consists of 169 students, and a sample of 42 respondents was selected through random sampling. Data were collected using questionnaires and documentation, then analyzed using validity, reliability, normality, linearity, and Pearson Product Moment correlation tests. The findings show that teacher leadership implementation is at a fairly good level with an average score of 70, while students’ Fiqh achievement is at a moderate level with an average score of 92. The hypothesis test yields a correlation coefficient of 0.990, indicating a strong and significant positive relationship between teacher leadership and students’ Fiqh achievement. The implication of this study suggests that improving teacher leadership through professional development and pedagogical competence enhancement can significantly foster better learning outcomes and character building among students in tahfidz-based Islamic boarding schools.